2001
DOI: 10.1007/s11745-001-0712-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conjugated linoleic acid on plasma lipoproteins and tissue fatty acid composition in humans

Abstract: Conjugated linoleic acid (CLA) has been suggested by some animal studies to possess antiatherogenic properties. To determine, in humans, the effect of dietary CLA on blood lipids, lipoproteins, and tissue fatty acid composition, we conducted a 93-d study with 17 healthy female volunteers at the Metabolic Research Unit of the Western Human Nutrition Research Center. Throughout the study, subjects were fed a low-fat diet [30 energy percent (en%) fat, 19 en% protein, and 51 en% carbohydrate] that consisted of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
84
5
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 37 publications
13
84
5
4
Order By: Relevance
“…Our analysis showed that TAG level decreased nonsignificantly after intake of either CLA supplements or CLA-enriched foods, similar to previous studies on either enriched foods or CLA supplements. Some findings suggested that CLA had no significant effect on TAG concentration (11)(12)(13)(14)(15)(16)(17)(18)(19)21,22,(24)(25)(26)(27)(29)(30)(31)(32)(33)(34)36,40,(47)(48)(49)(50)(51)(52)(53)(55)(56)(57)(58)(59) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis showed that TAG level decreased nonsignificantly after intake of either CLA supplements or CLA-enriched foods, similar to previous studies on either enriched foods or CLA supplements. Some findings suggested that CLA had no significant effect on TAG concentration (11)(12)(13)(14)(15)(16)(17)(18)(19)21,22,(24)(25)(26)(27)(29)(30)(31)(32)(33)(34)36,40,(47)(48)(49)(50)(51)(52)(53)(55)(56)(57)(58)(59) .…”
Section: Discussionmentioning
confidence: 99%
“…(2001) (58) Seventeen females, healthy normalweight (11) Twenty-five males, healthy overweight and obese (18) 401 males and females, healthy overweight and obese…”
Section: -68mentioning
confidence: 99%
“…A 6.4 g day 21 MI-CLA doses for 12 weeks produced a modest increase in lean mass (0.6 kg) but significant decrease in serum HDL-cholesterol, sodium, hemoglobin, and hematocrit, and significant increases in serum alkaline phosphatase, C-reactive protein, and K-6, and white blood cells. Plasma triacylglycerides (TAG) did not significantly change or decrease compared to placebo in some studies with MI-CLA supplementation 33,59,62,63 . Nevertheless, in another study mean plasma TAG concentration was higher during supplementation with a mixture 85% trans-10,cis-12 CLA than with another mixture 80% cis-9,trans-11 CLA 24 .…”
Section: Metabolic Effects Of Conjugated Linoleic Acidmentioning
confidence: 99%
“…O panorama atual a respeito dos efeitos benéficos do CLA na redução dos lípides sangüíneos e na redução da aterosclerose apresenta resultados positivos em coelhos 71 e alguns em hamsters 72,73 . Em humanos os resultados não são satisfatórios, visto que a maioria dos estudos não demonstra alteração do perfil lipídico [74][75][76] e, quando isto acontece, essas alterações não são benéficas como, por exemplo, aumento na concentração de lipoproteina 77 , redução de HDL colesterol (principalmente pelo isômero trans-10, cis-12) e aumento de triacilglicerol 65,78 , além do aumento de LDL colesterol 79 . Destaca-se que os estudos realizados com humanos apresentam as mais diversas populações e amostragens relativamente pequenas contendo a menor 17 indivíduos 74,76 e a maior 180 indivíduos 77 .…”
Section: Cla Metabolismo De Glicose E Lipídeos E Composição Corporalunclassified
“…A partir de então muitos foram os estudos com diversos animais [102][103][104] , com culturas de adipócito de roedores e humanos [105][106][107][108][109] e com humanos 8,65,[74][75][76][77][78][79][80]90,95,96,[110][111][112][113][114][115][116] , que surgiram com o objetivo de avaliar a propriedade de redução da gordura corporal, bem como elucidar os mecanismos de ação pelos quais o CLA desempenha esse papel.…”
Section: Cla Metabolismo De Glicose E Lipídeos E Composição Corporalunclassified